We'll have to repeatedly square both sides of the equation, in order to get rid of the square roots. Squaring a first time yields
![19+\sqrt{30+√(32+x)}=25](https://img.qammunity.org/2021/formulas/mathematics/middle-school/m98zs8kevqoqgyav4jsnshnn52whrjdm0b.png)
Move the 19 to the right hand side:
![\sqrt{30+√(32+x)}=6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rvk7hckuo8d1u0punrtcj5imqzw6fvulc8.png)
And square again:
![30+√(32+x)=36 \iff √(32+x)=6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/knwrc4qsuyepd0bbjdb2wbdcammnm3fbnr.png)
Square one last time:
![32+x=36 \iff x=36-32=4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y0xx5s6ze55wu5g7j2kcd0ofilyh13j74v.png)
Let's check the solutions: all these squaring might have created external solutions:
![\sqrt{19+\sqrt{30+√(32+4)}}=\sqrt{19+√(30+6)}=√(19+6)=√(25)=5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nw8ox01b8lnk2t2ze5cg6wd4c0mwwvzwkt.png)
So,
is a feasible solution.